Financiamento do SUS: análise dos impactos na gestão do Hospital Universitário da UFSCar no período de 2017 a 2020 - Casonato, Fábio Antonio (Universidade Federal de São Carlos, 2022)
Faced with a scenario of budget constraint faced by Public Health in Brazil, it is essential to understand how the resources invested by the State are being spent by public entities, since the population, due to the payment of a high tax burden to the government, has been demanding more and more efficiency in the services provided to the community. The objective of this study is to analyze the extent to which SUS funding impacts the financial management of the University Hospital of the Federal University of São Carlos (HU-UFSCar), currently managed by the Empresa Brasileira de Serviços Hospitalares (EBSERH). For this, financial information was collected on the entity's revenues and billing in the years 2017, 2018, 2019 and 2020. The values of the procedures performed by the hospital in this period referenced by the SUS Table were converted into values charged by the market based on the Classification Brazilian Hierarchy of Medical Procedures (CBHPM). Comparing the values obtained with the costs for carrying out the procedures, it was found that, if the services were performed by the private sector, the population would pay a higher amount for the same services that are offered by the HU-UFSCar in the public regime. Efficiency in the use of resources by the entity was also observed, since the value produced is higher than the value used to perform the services. Finally, it was not possible to observe the effects of underfunding, existing in Brazilian health, on the financial management of the HU-UFSCar because, with the installed capacity, the Hospital performed a large number of outpatient procedures and hospitalizations in the studied period at a cost lower than the values practiced by the market.
SUS financing: analysis of impacts on the management of the University Hospital of UFSCar from 2017 to 2020
Keywords: Gestão pública; Saúde pública; Financiamento da Assistência à Saúde; Hospital Universitário Federal; Governança pública; Public administration; Public health; Health Care Financing; Federal University Hospital; Public Governance; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA::CONTABILIDADE E FINANCAS PUBLICAS